Data Analytics in Management Accounting: A Tool For Strategic Decision-Making in Competitive Markets (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The advancement of information technology, particularly in data analytics, has significantly impacted management accounting practices and strategic decision-making. This study aims to analyze the role of data analytics in management accounting and its impact on strategic decision-making in competitive markets. This study proposes a new framework that integrates data analytics into management accounting, focusing on its application in improving decision-making accuracy, competitive advantage, and operational efficiency. The methodology employed is a literature-based review, examining relevant journal articles, books, and industry reports. Secondary data is used to assess the impact of data analytics in management accounting and strategic decision-making. The findings reveal that the implementation of data analytics in management accounting improves budgeting and forecasting accuracy, provides a competitive advantage through faster market responses, and enhances operational efficiency by reducing costs and streamlining processes. The analysis indicates that while there are challenges such as technological barriers, organizational resistance, and ethical issues, the opportunities presented by data analytics in management accounting are significant. Proper implementation can support more accurate and efficient strategic decision-making, improving a company’s competitive positioning. Future research could focus on exploring the application of emerging technologies like artificial intelligence (AI) and machine learning in management accounting. Additionally, further investigation into the impact of data privacy regulations and ethical challenges is needed.